The Effect of Tilt Angle of Axial Fan Blades on Air Flow Distribution in the Cabinet Dryer: Simulation Study Using Computational Fluid Dynamics - Saputra, Agus Dian; Pratoto, Adjar; Gusriwandi, Gusriwandi; Suprianto, Joko (Universitas Negeri Padang, 2021)
The application of tray dryer is widely used for various commodity dryers due to its simple construction. However, one of the drawbacks of tray dryer is the uneven airflow distribution in the drying chamber which results in the drying rate in the tray position being unequal. As a result, the degree of dryness of the product also varies. This study investigated the effect of fan blade angle on airflow distribution in the dryer cabin through numerical simulations. The axial fan diameter was 350 mm with a thickness of 20 mm. The variations of axial fan blades used were 10o, 20o, 30o and 45o. The number of blades used was 4, and the allowable airflow limit was 2 m x 1 m x 1 m, with an axial fan rotation of 500rpm. Based on the simulation results, the 45o fan angle had good air distribution results compared to the 10o, 20o, and 30o fan angles. Likewise, the distribution of air produced by the fan was evenly distributed, because the greater the angle of the fan used for the dryer, the better the results would be obtained.